Analisis Implementasi Pemeriksaan Refraksi sebagai Bagian dari Manajemen Kualitas Layanan Optik Brayan Depok Tahun 2025: Taufik Hadi - Taufik Hadi (STIKes Persada Husada Indonesia, 2026)
Refraction examination is one of the main pillars of optical services, playing a crucial role in determining the accuracy of refractive error diagnosis and the provision of appropriate visual correction. The implementation of refraction examination not only reflects the clinical competence of optometry personnel but also serves as an indicator of the overall quality of optical service management. Inaccurate examinations may lead to visual discomfort, reduced productivity, and decreased patient trust in optical services. This study aims to analyze the implementation of refraction examinations as part of optical service quality management, emphasizing procedural accuracy, compliance with standard operating procedures (SOPs), and their impact on patient satisfaction and loyalty. This study employed a mixed-methods approach. Quantitative data were collected through questionnaires administered to 100 patients from five optical service units in the Jakarta area, while qualitative data were obtained through in-depth interviews with 15 optometrists and 5 optical managers. Quantitative analysis was conducted using multiple linear regression, and qualitative data were analyzed thematically to identify quality management patterns and barriers to implementation. The results indicate that the accuracy of refraction examinations, clarity of communication regarding examination results, and compliance with SOPs significantly affect patient satisfaction (p < 0.05), contributing 42%, 28%, and 18%, respectively. Optical units with internal quality monitoring systems and regular training demonstrated higher service consistency. The main barriers identified include limited service time, variations in SOP understanding, and limited examination equipment.